LEGACY APPLICATIONS MIGRATION PROCESS OVER CLOUD- A REVIEW - Gajendra Shrimal, Kavita (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2016)
Cloud is the buzzword of the moment. Without a process in place, there’s a chance you will get into problems such as a successful migration requires well-defined process support, and the same is true for migrating legacy applications to the cloud. This paper attempts to analyze existing process models in order to identify gaps, and then propose a process framework that will aid in the migration of legacy applications to cloud platforms effectively. Computing resources are provided as services in the cloud computing model. The underlying unit of deliverable functionality resources is the service. Key words: Cloud technology, Cloud model, Migration process